Data Logger Digital Berbasis ATmega 2560 - Alhidayatuddiniyah T W; Siwi Puji Astuti; Santy Handayani (UNIVERSITAS INDRAPRASTA PGRI, 2019)
In this research, a data logger has been created to record the measurement results of current and electric voltage from a solar power system and wind power. This study aims to make a current and voltage measurement data recorder automatically so that the data retrieval process is easier and more accurate. Data loggers have 10bit ADC accuracy and data can be stored in a Micro SD Card. Data recording by a data logger is done every 100 ms for twenty-four hours then the data is plotted. The results of seven days of collecting current and voltage data for solar power plants obtained graphs such as square waves with maximum voltage and current are 33 volts and 537 mA, for wind power systems the maximum voltage and current were 26 volts and 273 mA. The memory used to record for one day is 5.2MB so the data logger is able to measure the current and voltage of the power generation system and record the measurement data for twenty-four hours continuously